INCIDENCE DU LANCEMENT DE LA BIERE PRIMUS SOUS LE LABEL PETITE YA QUARTIER PAR LA BRALIMA SUR LA CONSOMMATION A KINDU EN 2016 - ABAVUME, TAMBWE (IJRDO - Journal of Business Management, 2022)
The brewing sector is marketed by the permanent and active search for the implementation of niew strategies in order to face up to real competition ; the goal is to maximize sales through new ones. The main concern of this research is to know why BRALIMA decided to launch PRIMUS beer on the market under the PETITE YA QUARTIER label. Thus, we argued that this decision was motived by the desire to attract the greatest number of customers through a strategy of psychologically lowering the price. Indeed, the interpretation of the results from the statistical processing of our data reveals that this strategy has a positive impact on the consumption of PRIMUS beer in Kindu, because the estimate of monthly consumption one year after the launch (2016) is more than double that observed before (2015).